2020
DOI: 10.1007/s11356-019-07570-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis optimisation and characterisation of chitosan-calcite adsorbent from fishery-food waste for phosphorus removal

Abstract: Here, Box-Behnken design (BBD) approaches were utilised to optimise synthesis methodology for the chitosan-calcite rich adsorbent (CCM) made from fishery-food waste material (crab carapace), using low-temperature activation and potassium hydroxide (KOH). The effect of activation temperature, activation time and impregnation ratio was studied. The final adsorbent material was evaluated for its phosphorus (P) removal efficiency from liquid phase. Results showed that impregnation ratio was the most significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 49 publications
0
9
0
1
Order By: Relevance
“…The wastewater from the primary settling tank of a WWTP was used as a P source for MA production [50,51]. The production of crab carapace material (CCM) from ERI-Veolia employed thermochemical modification using potassium hydroxide (KOH) to deacetylate the chitin chain of crab carapace (Cancer pagurus) and dry it at 105 • C to create a chitosan-calcite adsorbent [52,53]. The absorbent was then applied in Veolia's pilot reactor FILTRAFLO TM -P that uses gravitational wastewater filtration through an adsorption media with continuous self-backwashing.…”
Section: Fertilizing Products Analysismentioning
confidence: 99%
“…The wastewater from the primary settling tank of a WWTP was used as a P source for MA production [50,51]. The production of crab carapace material (CCM) from ERI-Veolia employed thermochemical modification using potassium hydroxide (KOH) to deacetylate the chitin chain of crab carapace (Cancer pagurus) and dry it at 105 • C to create a chitosan-calcite adsorbent [52,53]. The absorbent was then applied in Veolia's pilot reactor FILTRAFLO TM -P that uses gravitational wastewater filtration through an adsorption media with continuous self-backwashing.…”
Section: Fertilizing Products Analysismentioning
confidence: 99%
“…It has been reported that chitosan, which is a deacetylated form of chitin, reduced serum phosphorus in rats (Baxter et al, 2000). According to Pap et al (2020), chitosan can bind to phosphorus via its amine group (-NH 2 ), and the similar structure of chitin with chitosan may explain the observed decrease in serum phosphorus. The CPK level decreased in the 50HILM group, which may be ascribed to the low muscle mass caused by the lower final body weight of HILM-fed broilers (Garcia and Creatine, 1974;Yen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pap et al. (2020) [70] found an adsorbent capacity for P of 76.9% of the initially provided 0.02 g P L –1 on lab‐scale. This capacity was even higher for modified mussel shell powder used for microalgae immobilization with P removal rates of 88% from initial 0.1025 g L –1 on lab‐scale [71].…”
Section: P In Food and Food Processing Wastesmentioning
confidence: 99%